Soured on the system disaffected men in 20th century American film - Schultz, Robert T. (McFarland & Co., Inc., Publishers, 2012)
"This work analyzes popular films produced in the years of significant historical change from 1946 to the end of the twentieth century. Disaffected male characters represent traditional values of independent thought and action as they negotiate life in the "organized system" (corporate life and the consumer culture) increasingly demanding dependence and conformity, which they resist"--